A Novel Fuzzy Modifier Interpolation Rule for Computing With Words - Aggarwal, Swati; Dadu, Tanvi; Aggarwal, Nisha (Informatica, 2022)
Computing with Words(CW) is a concept that is used to solve problems with input in natural language. Modifiers are transformation functions with predefined labels used extensively in the decision making systems to specify the desired value of a linguistic variable defined by fuzzy sets. In previous works, significant effort has been made to study the application of CW in many domains ranging from fraud detection systems to diagnosis systems in medicine. However, the application of CW in these fields with modified fuzzy sets didn't give satisfactory results. The existing interpolation rule, when applied to modified fuzzy sets, does not take care of the extreme left and extreme right-shifted fuzzy sets. Hence, there is a need to introduce a new interpolation rule when working with modifiers. In this paper, we propose a new Fuzzy Modifier Interpolation Rule to Type-1 Fuzzy sets and Interval Type-2 Fuzzy Sets to enhance the quality of results obtained when modifiers are applied.